The Effect of CEO Power on Firm Value: The Moderating Role of Firm Size - Wibowo, Andika Nur Dzaky; Anna Retnawati (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
This study provides new empirical evidence on how CEO power—proxied by insider status, tenure, and financial expertise affects firm value within Indonesian state-owned enterprises (SOEs), and how firm size moderates this relationship. Unlike prior studies focusing mainly on private firms or developed markets, this research highlights the unique governance dynamics of SOEs that operate under dual mandates of profitability and social responsibility. Using 135 firm-year observations from 2019–2023 and panel regression with interaction terms, the findings reveal that CEO insider status and financial expertise significantly reduce firm value, whereas CEO tenure has no direct effect. Importantly, firm size mitigates the negative influence of CEO insider and financial expertise, suggesting that larger SOEs possess stronger governance mechanisms capable of constraining excessive managerial power. These results extend agency theory by demonstrating that the governance effectiveness of CEO power depends on organizational scale and ownership context. This study contributes to the corporate governance literature by offering context-specific evidence from emerging markets and providing practical implications for policymakers to strengthen oversight in smaller SOEs to preserve firm value.